Efficacy test of biological agent Trichoderma spp. against white root fungus disease (Rigidoporus microporus) in rubber tree (Hevea brasiliensis) - Tri Rapani Febbiyanti; Risal Ardika; Anita Setyawati (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2026)
White root rot disease caused by Rigidoporus microporus is one of the most destructive root diseases in rubber plantations, leading to significant yield losses each year. The study aimed to evaluate the efficacy of the biological control agent Trichoderma spp. in suppressing the development of white root fungus on rubber seedlings. Laboratory assays using the dual culture method and greenhouse trials with preventive and curative applications were conducted, involving treatments with Trichoderma-based biofungicide, chemical fungicide, and control. Laboratory results showed that Trichoderma spp. inhibited the growth of R. microporus by more than 44% on the fifth day after inoculation. In greenhouse experiments, preventive application of Trichoderma spp. was more effective than curative application, as indicated by improvements in stem diameter, plant height, and the number of leaves. Besides antagonistic activity, Trichoderma spp. contributed to improved soil fertility and plant growth. The lowest disease intensity (25.2%) was observed in the preventive treatment with Trichoderma, while in curative treatments, its effectiveness was comparable to that of chemical fungicides. The findings confirm that Trichoderma-based biofungicides are effective in controlling white root rot disease while simultaneously enhancing plant growth, making them a sustainable alternative to chemical fungicides.